Evaluation of Some Plant Extract and Bio- Fungi to Control Leaf Spot of Safflower Plant Disease - LAYLA A. BENYAN (University of Thi-Qar Journal of agricultural research, 2024)
This research study aims at evaluating the effectiveness of the biological fungus Trichoderma longibrachiatum , Trichoderma harzianum and some plant extracts  kinocarpus( Leucaena leucocephala) ,Eucalyptus (Eucalyptus camaldulensis), henna leaf extract ( Lawsonia inermis ). Besides, finding the best concentrations of plant extracts to stimulate the systemic resistance to safflower plant Carthamus tinctorius, against alternaria leaf spot. The results made clear that the fungus Alternaria alternata had  clear effect in reducing the percentage of germination of safflower seeds as the rate reached 53.33% while the percentage of seedling damping off reached 81.11% compared with control treatment 93.33, 0 % respectively.The biological fungi have high effectiveness with inhibiting growth of  fungus Alternaria alternata, according to results  as the  antagonisim level  was (1) as in bell scale. Plant extract also gave a high efficiency in preventing the infectious fungus's growth as rate of  kinokarpus , henna, eucalyptus reached 75.78 ,74.59 , 70.64 % respectively. Effect of the extracts in inhibiting the  pathogenic fungus went up with increased concentration, as the highest percentage of inhibition was reached at a concentration of 10 % for tested extracts, the kinocarpus plant gave the highest rate reached 91.51%, while the percentage reached 89.62, 80.36 % for henna and eucalyptus extract, respectively.